DESIGN OF AUTOMATED ILLUMINANCE IN THE READING ROOM BASED ON MICROCONTROLER ARDUINO - Nurrachim Fanny Nahwan; Sumarna Sumarna (Prodi Fisika, Departemen Pendidikan Fisika, 2016)
The goal of this study was to design and create an automatic tool to control luminousintensity in reading room using Arduino. The design consisted of three blocks, they were thesensor circuit, the conditioning circuit, and display circuit. The sensor circuit was provided tocapture the change of the luminous intensity in the reading room. The conditioning circuitconsisted of stepper motor, dimmer, and microcontroller. They were used as a regulator forthe tool. The display circuits was provided to facilitate the reading of luminous intensitydetected by the sensor. Data were collected by recording the change in luminous intensitythat displayed and recording the change in time to settle with a smartphone’s stopwatch. Theresults of the recording were synchronized and recorded in the table of respontime. Theautomatic tool works to stabilize the light intensity at (145-155) lux. The tool will continue towork as long as the reading of lominous intensity in the room is not conform with the setprogram. Speed of the automatic tool was towards to setting point depend on rotational speedof stepper motor which controlled via Arduino program.Key word: Illuminance automated, reading room, microcontroller Arduino.